(untitled) (American Journal of Islam and Society, 2002)
Beyond Turk and Hindu grew out of a collection of papers presented at a conference on "Islam in South Asia," held at Duke University in April 1995. It has 3 sections, 13 chapters, 8 photographs, 3 maps, 2 tables, a glossary, and an index. The book deals with the broad subject of civilizational interfaces in the South Asian context. It belongs to the category of interfaith relations and is addressed to a general audience interested in the Hindu-Muslim dialectic. The authors do not accept the premise that interreligious differences in South Asia are set and irreconcilable. To quote the editor: "We vigorously contend that there is a larger point to make, namely, that the constant interplay and overlap between Islamic and Indic worldviews may be at least as pervasive as the Muslim-Hindu conflict ... " This position is a challenge to those scholars who view India and Pakistan as embodiments of two separate religious identities. Section One contains three essays on textual analysis to assess the sameness and otherness of identity formation. The authors do not avoid the controversies that are bound to emerge from the sometimes disparaging tenns used by Hindus and Muslims to refer to each other, or the animosities that have emerged from the desecration of mosques and temples: Arabic and Persian use of the term Hindu had a range of meanings that changed over time, sometimes denoting an ethnic or geographic referent without religious content. Similarly, Indic texts referring to the invaders from the northwest used a variety of terms in different contexts, including yavanas, m/ecchas,farangis, musafmans, and Turks. These terms sometimes carried a strong negative connotation, but they rarely denoted a distinct religious community conceived in opposition to Hindus. In and of themselves, however, such terms tell us little. To understand the usage of these terms, one must move beyond the terminology itself- beyond Turk and Hindu - to analyze the framing categories and generic contexts within which these terms are used. The authors illustrate the power of bidirectional cultural forces by offering the example of the Punjab’s Bulle Shah and Bengal’s mystical Satya Pir. Bulle Shah, a contemporary of Shah Waliullah of Delhi, lived in the late ...